2017
DOI: 10.1037/men0000117
|View full text |Cite
|
Sign up to set email alerts
|

Student veterans’ self-stigma of seeking help: Contributions of painful self-conscious emotions, traditional masculine norms, and war-zone service.

Abstract: Despite established connections between traditional masculinity ideologies and self-stigma of seeking psychological help, few studies have examined relevant constructs in samples of veterans. The present study addressed this gap by testing a model specifying conformity to the masculine role norms of self-reliance and emotional control as mediating factors of the probable associations between painful self-conscious emotions (i.e., guilt and shame) and self-stigma of seeking help in a sample of student veterans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 61 publications
0
18
1
Order By: Relevance
“…It could be that beliefs that are specific to treatment-seeking are influenced by the cultural value of self-reliance, whereas general negative beliefs about mental health problems and anticipated stigma may be influenced by other cultural values, such as beliefs and values around health and well-being, and concerns about belonging. We also found no significant relations between emotional control and negative mental health related beliefs or anticipated stigma, in contrast with a prior study that revealed a significant relation between emotional control and general self-stigma (McDermott et al, 2017). The discrepancy between these studies could be due to differential measurement tools assessing these cultural values and stigma, consistent with a recent review of this literature, which raised the possibility that much of the inconsistency in stigma study findings may be due to the application of different conceptualizations and measurements of stigma (Fox, Earnshaw, Taverna, & Vogt, 2017).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It could be that beliefs that are specific to treatment-seeking are influenced by the cultural value of self-reliance, whereas general negative beliefs about mental health problems and anticipated stigma may be influenced by other cultural values, such as beliefs and values around health and well-being, and concerns about belonging. We also found no significant relations between emotional control and negative mental health related beliefs or anticipated stigma, in contrast with a prior study that revealed a significant relation between emotional control and general self-stigma (McDermott et al, 2017). The discrepancy between these studies could be due to differential measurement tools assessing these cultural values and stigma, consistent with a recent review of this literature, which raised the possibility that much of the inconsistency in stigma study findings may be due to the application of different conceptualizations and measurements of stigma (Fox, Earnshaw, Taverna, & Vogt, 2017).…”
Section: Discussioncontrasting
confidence: 99%
“…Two cultural factors that may be particularly relevant to anticipated stigma and negative mental health beliefs are emotional control and self-reliance. The first study to examine relations between emotional control and exaggerated self-reliance and dimensions of stigma found that emotional control and exaggerated self-reliance partially mediated the relation between guilt and shame, and self-stigma (McDermott, Currier, Naylor, & Kuhlman, 2017), in a sample of student veterans who deployed to a warzone (but not among non-deployed veterans). However, no research to our knowledge has examined of the relations between these cultural values (exaggerated self-reliance and emotional control) and specific dimensions of negative mental health beliefs (such as negative beliefs about mental health problems, treatments and treatment-seeking) and anticipated stigma.…”
mentioning
confidence: 99%
“…This indicates that masculine traits were significantly lower among firefighters with PTSD compared to those without. In contrast, masculinity was positively associated with PTSD in Latina women [21] and emotional control and self-reliance were positively associated with PTSD in male and female veteran students [22]. The latter two studies had relatively weak effect sizes.…”
Section: Masculinity Masculine Ideals and Masculine Gender-role Stressmentioning
confidence: 88%
“…It results in low-esteem, low self-efficacy, and failure to take advantage of health care opportunities (Corrigan and Watson, 2002). The hypothesis that self-stigma is associated with a negative attitude to seeking help for mental illness has been confirmed in diverse samples including students (Cheng et al, 2015, 2018; Jennings et al, 2015; McDermott et al, 2017; Mullen and Crowe, 2017). The Self-Stigma of Seeking Help Scale (SSOSH) assesses perceptions of the loss of self-esteem the respondent would feel if he or she decided to seek professional psychological help (Vogel et al, 2006).…”
Section: Introductionmentioning
confidence: 92%